2D material infrared photonics and plasmonics - Elbanna, Ahmed (2023)
Two-dimensional (2D) materials including graphene, transition metal dichalcogenides, black phosphorus, MXenes, and semimetals have attracted extensive and widespread interest over the past years for their many intriguing properties and phenomena, underlying physics, and great potential for applications. The vast library of 2D materials and their heterostructures provides a diverse range of electrical, photonic, mechanical, and chemical properties with boundless opportunities for photonics and plasmonic devices. The infrared (IR) regime, with wavelengths across 0.78 μm to 1000 μm, has particular technological significance in industrial, military, commercial, and medical settings while facing challenges especially in the limit of materials. Here, we present a comprehensive review of the varied approaches taken to leverage the properties of the 2D materials for IR applications in photodetection and sensing, light emission and modulation, surface plasmon and phonon polaritons, non-linear optics, and Smith-Purcell radiation, among others. The strategies examined include the growth and processing of 2D materials, the use of various 2D materials like semiconductors, semimetals, Weyl-semimetals and 2D heterostructures or mixed-dimensional hybrid structures, and the engineering of light-matter interactions through nanophotonics, metasurfaces, and 2D polaritons. Finally, we give an outlook on the challenges in realizing high-performance and ambient-stable devices and the prospects for future research and large-scale commercial applications.